Urgensi Tata Ruang Berbasis Mitigasi Bencana Likuifaksi: Hak Asasi Masyarakat Kabupaten Jember - M. Kava Zulfikri; Eddy Mulyono; Muhammad Bahrul Ulum (Badan Penelitian dan Pengembangan Hukum dan HAM, 2022)
The potential for high liquefaction in Jember Regency has the potential to take its toll and losses that will interfere with aspects of life as experienced by the Central Sulawesi in 2018. Disaster mitigation efforts are needed that look at the extent to which spatial planning and development in Jember Regency pay attention to liquefaction vulnerabilities. Because the vulnerability of the region itself is a consideration of spatial planning and development. This aricle aims to discuss the extent of the importance of liquefaction mitigation-based spatial planning in Jember in terms of regulations, impacts, and their relation to the fulfillment of the human rights of the people of Jember. The method used is socio-legal. This paper confirms that the regulation of decent and safe housing from liquefaction disasters in Jember is still minimal. In addition, the RTRW and RPJMD Regional Regulations have also not made liquefaction part of the disaster in Jember. However, the urgency of this liquefaction regulation is actually not only about disaster mitigation-based spatial planning but also the fulfillment of the human rights of liquefaction victims, so the government is obliged to regulate it even if there are no specific regulations at the national or local level.